ANALISA PERSEPSI SISTEM TIPPING STUDI KASUS KEPADA KARYAWAN CONCIERGE DI HOTEL BINTANG 4 DAN 5 DI SURABAYA - Jane Fredelia Ngadiman; Cindy Claudia Ezar (Jurnal Hospitality dan Manajemen Jasa, 2018)
Abstract: This study discusses the perception of the concierge employee about the tipping system that has been applied in 4 and 5 star hotels of Surabaya. This research uses descriptive qualitative method which also offers two scenarios to be asked to the informants, and from this research was taken 8 informants to be interviewed. The results obtained from this research is that the implementation of tipping has been run in every hotel but still not much research in Indonesia which emphasizes on the system tip. And 5 informants chose a no sharing tips system which is considered a fair system to be applied at the hotel. Detailed discussion is described in this study.Keywords:             Tip, Tipping System, Perceived Fairness.